The Impact of Bilingual Education on Young Children's Cognitive Development - Xia, Ning (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores the impact of bilingual education on the cognitive development of young children. It first defines bilingual education and its theoretical basis, and analyses in depth the definition, main stages, characteristics and influencing factors of young children's cognitive development. It is found that bilingual education significantly enhances young children's linguistic competence, executive functioning, creativity, problem-solving ability, as well as memory and information processing speed, while promoting intercultural understanding and social skills. However, challenges such as language confusion, delayed initial language development, and educational resource constraints need to be effectively addressed. The concluding section presents policy recommendations and directions for educational reform, emphasising the important roles of family and society in bilingual education. By integrating educational resources, enhancing teacher capacity and strengthening home-school cooperation, can maximise the positive impact of bilingual education and lay the foundation for the holistic development and future success of young children.